Hubungan Antara Empati Dengan Perilaku Prososial Pada Siswa SMK Batik Surakarta - Oktaviani, Anisa, Dra. Partini, M.Si (2017)
Prosocial behavior is an action taken or planned to help others regardless of the motives of the helper. One of the factors that influence the prosocial behavior is empathy. This study aims to determine: the relationship between empathy and prosocial behavior in students of SMK Batik 2 Surakarta. The level of empathy in students of SMK Batik 2 Surakarta. The level of prosocial behavior in students of SMK Batik 2 Surakarta. The amount of the effective contribution of empathy and prosocial behavior in students of SMK Batik 2 Surakarta. Researchers used quantitative methods and techniques of data collection using random cluster sampling to achieve the objectives of this research. Subjects used in this study a number of 117 subjects and are used Class XI SMK Batik 2 Surakarta. In conclusion, there is a significant positive relationship between empathy and prosocial behavior. The results shown by the correlation coefficient r xy = 0,462 with sig. = 0,000; (P <0.01). Variable levels of empathy in the high category. The mean empirical (RE) for the variable empathy alone is 95.16 and the mean hypothetical (RH) of 80. The level of empathy variable prosocial behavior in the high category. The mean empirical (RE) amounted to 118.39 and the mean hypothetical (RH) 92.5 prosocial behavior variables. Effective donations between empathy and prosocial behavior in students by 21.3%, indicated by the correlation (r2) = 0.213. This means there are 78.7% of other factors that influence prosocial behavior.